The RNA Worrld : The nature of modern RNA suggests a prebiotic RNA world - Gesteland, Raymond F (Cold Spring Harbor Laboratory Press, 2006)
"Recent studies on the activities of RNA in the cell have revolutionized our understanding of the many roles played by this molecule. The first two editions of The RNA World (1993, 1999) shed light on the pre-biotic era dominated by this versatile molecule, and provided an overview of the state of RNA research at the time. The new third edition of The RNA World updates this perspective.